Forever starts now - London, Stefanie (Amara, 2021)
"Monroe Roberts...knocked “forever” permanently off her wish list ever since the love of her life skipped town with the cliché yoga instructor...She's got this struggling diner to keep her busy, trying anything to boost sales- until a hot Australian strolls in...Monroe's restaurant is packed full of women who aren't there to order food, unless Ethan is on the menu. This could sink her business faster than ever. So- light bulb- what if they pretend to be together?"--